Technology and economic theory - Stan Metcalfe (Max Planck Institute of Economics, 2009)
Technology and technological change play a central role in economics, whether in the theory of resource allocation or in the theory of growth and development. Yet the nature of technology is largely ignored in economic theory, it being considered sufficient to treat technology as a constraint on productive opportunities. This short essay delves a little deeper into the nature of technology and the material, energy and information transformation processes that it represents. A deeper understanding of technology leads to a deeper understanding of the main currents of technological advance and to the reasons why the development of technology and its application are so uneven over time and place.
Keywords: 330; Technologie; Technischer Fortschritt; Wirtschaftstheorie